Characterization of Oil-in-Water Emulsions Prepared with Triblock Copolymer Poloxamer 407 and Low-Molecular-Mass Surfactant Mixtures as Carriers of Grape Pomace Waste Polyphenols - Veljko S. Krstonošić; Darija B. Sazdanić; Dejan M. Ćirin; Ivana R. Nikolić; Miroslav S. Hadnađev; Milica T. Atanacković Krstonošić (MDPI AG, 2024)
Background: Natural antioxidants, such as grape pomace polyphenols, can be extracted by a surfactant-based green technology and incorporated into various emulsions. Therefore, this work aimed to investigate the physical stability and rheological characteristics of oil-in-water emulsions stabilized with poloxamer 407 (P407) and its mixtures with the low-molecular-mass surfactants Brij S20 (BS20) and Tween 60 (T60). Also, the influence of polyphenolic grape pomace extracts on the physical stability and rheological characteristics of the emulsions was examined. Methods: Grape pomace polyphenols were extracted by aqueous solutions of P407 and BS20/P407 and T60/P407 mixtures. Two different types of oil-in-water emulsions were examined: emulsions prepared with pure surfactants and emulsions prepared with surfactant-based polyphenol extracts of grape pomace. Both types contained 20% sunflower oil. Characterization of the emulsions comprised droplet size evaluation, rheology characteristics and creaming stability. Results: All the emulsions showed shear-thinning flow, while the rheological characteristics and creaming instability depended on the proportion of P407 in the emulsifier mixtures. Incorporation of grape pomace extracts had no effect on the investigated properties of the emulsions. Conclusion: The presence of extracted polyphenols in emulsifier mixtures had no significant effects on the emulsions' physico-chemical characteristics and stability. Therefore, the investigated emulsions can be considered suitable carriers for polyphenol-rich extracts.